Anxiety in the practice of a gynecologist. A psychiatrist’s view - Vasileva A.V. (РМЖ. Мать и дитя, 2018)
Anxiety in the practice of a gynecologist. A psychiatrist’s view Vasileva A.V. V.M. Bekhterev National Medical Research Center for Psychiatry and Neurology, St. Petersburg North Western State Medical University named after I.I. Mechnikov, St. Petersburg The article considers the main groups of anxiety disorders, which are most commonly met in the everyday practice of a gynecologist. Current studies indicate that there is a relationship between sex hormones and the systems of emotional brain regulation. The article determines the main groups of gynecological pathology (premenstrual syndrome, pregnancy, assisted reproductive technologies, climacteric period, oncogynecology), accompanied by affective and psycho-vegetative disorders, requiring complex treatment and appointment of psychopharmacotherapy. The main problems of differential diagnosis are identified taking into account the common links in the pathogenesis of gynecological and mental disorders. The possibilities of treating the anxiety disorders by a gynecologist are presented. The mechanisms of the action of tranquilizers and the strategy of choosing drugs for the treatment of anxious and psycho-vegetative disorders are described in detail. It is shown that tofisopam (Grandaxin) can be used as the drug of choice: it differs from traditional benzodiazepines and has a number of unique properties, namely, it does not have the risk of the drug-dependence formation and myorelaxation effect, that is, it can be administered to patients in outpatient practice and in situations requiring concentration of attention and making the right decisions. Key words: anxiety disorders, illness anxiety disorder, premenstrual tension syndrome, climacteric syndrome, menopause, tranquilizers. For citation: Vasileva A.V. Anxiety in the practice of a gynecologist. A psychiatrist’s view // RMJ. 2018. № 5(I). P. 51–55.